Variable Herz–Morrey estimates for rough fractional Hausdorff operator - Hussain, Amjad; Khan, Ilyas; Mohamed, Abdullah (Journal of inequalities and applications, 2024)
As a first attempt, we obtain the boundedness of the rough fractional Hausdorff operator on variable exponent Herz-type spaces. The method used in this paper enables us to study the operator on some other function spaces with variable exponents.